2002
DOI: 10.1029/2001jd001572
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol optical properties during INDOEX based on measured aerosol particle size and composition

Abstract: [1] The light scattering and light absorption as a function of wavelength and relative humidity due to aerosols measured at the Kaashidhoo Climate Observatory in the Republic of the Maldives during the INDOEX field campaign has been calculated. Using sizesegregated measurements of aerosol chemical composition, calculated light scattering and absorption has been evaluated against measurements of light scattering and absorption. Light scattering coefficients are predicted to within a few percent over relative hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 23 publications
0
21
1
Order By: Relevance
“…21). Despite this rapid decrease away from the coasts, the aerosol mass loading over much of the northern Indian Ocean is nevertheless substantial, even up to several hundred km downwind, e.g., at KCO, where the mean aerosol dry mass density was measured using cascade impactors and filter samplers and found to be 17 µg/m 3 for supermicron aerosols, and ranged from 19-22 µg/m 3 for submicron aerosols in polluted, highly scattering airmasses, down to ∼8 µg/m 3 in low scattering airmasses (based on the instrument intercomparison and aerosol properties analysis in Clarke et al, 2002, and on the overview of , which makes use of the measurements described in Chowdhury et al, 2001, andEldering et al, 2002). The submicron aerosol lies between the mean values of 15 µg/m 3 for suburban air pollution and 33 µg/m 3 determined for urban pollution in North America and Europe (Heintzenberg, 1989; unfortunately, despite the vast wealth of observations -or perhaps due to it -there are no comprehensive overviews of regional mean aerosol mass densities following up on this study).…”
Section: Aerosolsmentioning
confidence: 99%
“…21). Despite this rapid decrease away from the coasts, the aerosol mass loading over much of the northern Indian Ocean is nevertheless substantial, even up to several hundred km downwind, e.g., at KCO, where the mean aerosol dry mass density was measured using cascade impactors and filter samplers and found to be 17 µg/m 3 for supermicron aerosols, and ranged from 19-22 µg/m 3 for submicron aerosols in polluted, highly scattering airmasses, down to ∼8 µg/m 3 in low scattering airmasses (based on the instrument intercomparison and aerosol properties analysis in Clarke et al, 2002, and on the overview of , which makes use of the measurements described in Chowdhury et al, 2001, andEldering et al, 2002). The submicron aerosol lies between the mean values of 15 µg/m 3 for suburban air pollution and 33 µg/m 3 determined for urban pollution in North America and Europe (Heintzenberg, 1989; unfortunately, despite the vast wealth of observations -or perhaps due to it -there are no comprehensive overviews of regional mean aerosol mass densities following up on this study).…”
Section: Aerosolsmentioning
confidence: 99%
“…Eldering et al, 2002;Nessler et al, 2005;Schmid et al, 2006) have begun to investigate hygroscopic growth effects on the absorption coefficient which have been neglected in this study. Nessler et al (2005) found, at their observation site in central Europe, that although the effect on σ abs was significant, the consequent impact on the total σ ext was smaller than a 0.02% increase due to the small contribution of σ abs relative to that of σ sca .…”
Section: Aerosol Optical Depthmentioning
confidence: 99%
“…Many ambient measurements of the light scattering enhancement factor f (RH)=σ sp (RH)/σ sp (dry) were performed during the last 40 years (Covert et al, 1972;Sheridan et al, 2001;Eldering et al, 2002;Kim et al, 2006;Haywood et al, 2008;Yan et al, 2009), but just a few included measurements on the metastability of aerosol particles (Rood et al, 1987;Carrico et al, 2003;Wang et al, 2007;Fierz-Schmidhauser et al, 2009).…”
Section: Introductionmentioning
confidence: 99%